A Negative Regulator of Cellulose Biosynthesis, bcsR, Affects Biofilm Formation, and Adhesion/Invasion Ability of Cronobacter sakazakii - Gao, Jian-xin; Li, Ping; Du, Xin-jun; Han, Zhong-hui; Xue, Rui; Liang, Bin; Wang, Shuo (Frontiers in Microbiology, 2017)
Cronobacter sakazakii is an important foodborne pathogen that causes neonatal meningitis and sepsis, with high mortality in neonates. However, very little information is available regarding the pathogenesis of C. sakazakii at the genetic level. In our previous study, a cellulose biosynthesis-related gene (bcsR) was shown to be involved in C. sakazakii adhesion/invasion into epithelial cells. In this study, the detailed functions of this gene were investigated using a gene knockout technique. A bcsR knockout mutant (ΔbcsR) of C. sakazakii ATCC BAA-894 showed decreased adhesion/invasion (3.9-fold) in human epithelial cell line HCT-8. Biofilm formation by the mutant was reduced to 50% of that exhibited by the wild-type (WT) strain. Raman spectrometry was used to detect variations in biofilm components caused by bcsR knockout, and certain components, including carotenoids, fatty acids and amides, were significantly reduced. However, another biofilm component, cellulose, was increased in ΔbcsR, suggesting that bcsR negatively affects cellulose biosynthesis. This result was also verified via RT-PCR, which demonstrated up-regulation of five crucial cellulose synthesis genes (bcsA, B, C, E, Q) in ΔbcsR. Furthermore, the expression of other virulence or biofilm-related genes, including flagellar assembly genes (fliA, C, D) and toxicity-related genes (ompA, ompX, hfq), was studied. The expression of fliC and ompA in the ΔbcsR mutant was found to be remarkably reduced compared with that in the wild-type and the others were also affected excepted ompX. In summary, bcsR is a negative regulator of cellulose biosynthesis but positively regulates biofilm formation and the adhesion/invasion ability of C. sakazakii.